A Kaleidoscope of Hope: Exploring Experiences of Hope Among Service Users and Informal Carers in Health Care Contexts. (September 2017) - McCormack, Brendan; Borg, Marit; Cardiff, Shaun; Dewing, Jan; Jacobs, Gaby; Titchen, Angie; van Lieshout, Famke; Wilson, Valerie
Background: There is a large and diverse literature on the concept of hope in health care. This literature covers a broad spectrum of perspectives, from philosophical, conceptual, and theoretical analysis through to attempts at measuring the concept of hope with differing health care users.Aims: To explore the concept of hope through the secondary analysis of existing data sets, with the intention of understanding hope in the context of person-centeredness.Research Question: What is the experience of hope among service users and informal carers in different health care contexts?Method: Secondary analysis of data derived from three research studies.Findings: We identified four key themes that together illustrate what we describe as a kaleidoscope of hope, reinforcing the view that there is no one presentation of hope and that practitioners must engage authentically with service users to determine the most effective and appropriate intervention strategies.Conclusions: Hope is not a singular phenomenon, and in the context of person-centered practice there is a need for practitioners to engage authentically with service users and listen carefully to what may bring hope for them.